A 3.1-10.6 GHz HEMT Distributed Amplifier for Ultra-Wideband Application - Sepideh Ebrahimi; Alishir Moradikordalivand (Majlesi Journal of Electrical Engineering)
In this paper, a Distributed Amplifier (DA) by using HEMT technology for ultra-wideband application is presented. Creation of Distributed integrated circuit has been investigated for approximately seventy years rapidly to developing semiconductor process technologies in the modern IC design. By using of this method, multiple parallel signals are combined and obtain to increase the bandwidth, enhanced power combining amplitude, and novel design capabilities for IC process. The circuit was designed and simulated in ED02AH technology by using ADS2010. The 4-stage design achieves 15.5 dB of power gain (±0.5 dB) from 3.1 to 10.6 GHz. Reflected power of the input and output from loads matched to 50 Ohm are all below â10 dB over the bandwidth of the device, as is power transmitted from the output to the input. The device is stable for a wide range of input and output loads.